Study of Grain Boundary Character 2017
DOI: 10.5772/66598
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Segregation in Nanocrystructured Metallic Materials

Abstract: The aim of this chapter is to shed light on the effects of grain boundary segregation on microstructural evolution in nanostructured metallic materials as well as on their mechanical properties. Several key topics will be covered. First, a brief explanation of mechanical stress-driven grain growth in nanostructured Al, Ni, and Cu thin films will be provided in terms of a deformation mechanism map. It will become clear that the excess energy of grain boundaries enable the nanostructured metals to suffer from si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 105 publications
(215 reference statements)
0
1
0
Order By: Relevance
“…Figure 5 f also includes subunit T5, where the SF implies the dislocation lines, observed as a result of TB interaction. The HAADF-STEM examination confirmed that higher temperature was able to facilitate the progressive coalescence of two Ag (0) NPs into one larger Ag (0) NP with a fivefold twinned structure [ 49 ]. Additionally, we could suggest that the perfect anatase TiO 2 (101) may provide nucleation sites for the growth of Ag (0) NPs with a pentagonal bipyramidal structure ( Figure 5 c), which, unlike Ag (0) NPs with a planar (flat) geometry in Ag_TiO_LYO)/500 ( Figure 5 a–c), could support the improvement of the properties of Ag_TiO_LYO)/800 as a photocatalyst [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 f also includes subunit T5, where the SF implies the dislocation lines, observed as a result of TB interaction. The HAADF-STEM examination confirmed that higher temperature was able to facilitate the progressive coalescence of two Ag (0) NPs into one larger Ag (0) NP with a fivefold twinned structure [ 49 ]. Additionally, we could suggest that the perfect anatase TiO 2 (101) may provide nucleation sites for the growth of Ag (0) NPs with a pentagonal bipyramidal structure ( Figure 5 c), which, unlike Ag (0) NPs with a planar (flat) geometry in Ag_TiO_LYO)/500 ( Figure 5 a–c), could support the improvement of the properties of Ag_TiO_LYO)/800 as a photocatalyst [ 50 ].…”
Section: Resultsmentioning
confidence: 99%